Stakeholder selection for business processes support systems in interorganizational environments - Ballejos, Luciana C. (2005)
This work presents a methodology with basic steps to follow before developing Interorganizational Information Systems (IOSs), which constitute the support for the execution of business processes (BPs) in new structural forms made up of various organizations, called Interorganizational Networks (IONs). Then, a framework is given to describe IONs, analyzing different characteristics in three dimensions: organizational, interorganizational and technological and given real examples for them. The selection of stakeholders, one of the presented steps in the methodology, is a critical stage for this kind of projects. The dynamic interorganizational context in which IOSs-supported business processes are executed makes this task seriously difficult. For being applied on these contexts, an extended classification for stakeholders is given. Also, the strong link and influence existing between IONs characteristics and the stakeholders selection phase for this kind of environments is analyzed. Since specific attributes of each kind of networks are important and define the criteria for identifying stakeholders, basic selection criteria are deduced from the described analysis. This is particularly important in environments where cooperation and coordination among various organizations are the main objectives.